Catalytic fast co-pyrolysis of organosolv lignin and polypropylene over in-situ red mud and ex-situ HZSM-5 in two-step catalytic micro reactor - Ryu, Sumin; Lee, Hyung Won; Kim, Young-Min; Jae, Jungho; Jung, Sang-Chul; Ha, Jeong-Myeong; Park, Young-Kwon (ELSEVIER, 2020)
The additional use of red mud (RM) on the catalytic fast co-pyrolysis (CFCP) of organosolv lignin (OL) and polypropylene (PP) over ex-situ HZSM-5 was investigated using a tandem micro reactor system. Non-catalytic fast co-pyrolysis of OL and PP increased their decomposition efficiency owing to the effective interactions. The in-situ catalytic fast pyrolysis (CFP) of OL over RM led to the enhanced conversion of large molecular OL pyrolyzates with the additional production of aromatic hydrocarbons. The in-situ CFCP of OL/PP over RM resulted in a further increase in the cracking efficiency of OL/PP pyrolyzates as well as an increase in the aromatics formation efficiency owing to the effective interactions between their CFP intermediates. Furthermore, the application of RM in 1st in-situ catalytic reactor was found to be the optimal catalyst system because the in-situ CFCP of OL/PP over RM can enhance the formation of the proper hydrocarbons precursors for the production of aromatics over ex-situ HZSM-5 in 2nd reactor. Compared to the one-step CFCP of OL/PP over ex-situ HZSM-5, two-step CFCP of OL/PP over in-situ RM and ex-situ ZSM-5 maintained the higher aromatics formation during the 7 times sequential reaction due to the slow deactivation of ex-situ HZSM-5.
Keywords: HIGH-DENSITY POLYETHYLENE; LIGNOCELLULOSIC BIOMASS; COMPLETE OXIDATION; WASTE TIRE; OIL; CELLULOSE; KINETICS; ACID; TORREFACTION; CONVERSION